Sistem Infromasi Bimbingan Tugas Akhir Pada Prodi Manajemen Informatika Fakultas Sains Dan Teknologi Universitas Labuhanbatu - Tri Nizar Aulia (Journal of Student Development Information System (JoSDIS), 2022)
Along with the development of the world of information technology, now it affects many fields in the world of business, services, education and others. The world of education, especially universities, is one of the fields that is strongly influenced by developments in information technology. The current final project guidance system is generally manual, where students are guided by two supervisors, if students want to do final assignment guidance, they must look at a predetermined meeting schedule, then students come to the campus to meet with lecturers and provide guidance by bringing documents that want to be consulted. But the obstacles faced in the guidance process in this way is difficult to determine the suitability of time between lecturers and students so that the process of conducting guidance is hampered.To overcome some weaknesses, a Final Assistance Guidance System in the Information Management Study Program was designed. This system aims to design and build a guidance application that can provide convenience in the final project guidance process. The system is web-based, with the PHP and MYSQL programming languages as a database.